Development, In Vitro Characterization, Antitumor and Aerosol Performance Evaluation of Respirable Prepared by Self-nanoemulsification Method - Naseri, Neda; Zakeri-Milani, Parvin; Hamishehkar, Hamed; Pilehvar-Soltanahmadi, Younes; Valizadeh, Hadi (Drug Research, 2017)
Poor water solubility and low oral bioavailability limit the clinical application of Erlotinib as an anticancer. For this purpose, we encapsulated erlotinib in the solid lipid nanoparticles (SLN) and designed a spray-dried dry powder inhalable (DPI) formulation. Erlotinib-loaded SLNs were prepared using self-nanoemulsifying and characterized for physicochemical properties. Pulmonary deposition of spray-dried DPI formulation was performed using Next Generation Impactor. The particle size and zeta potential of Erlotinib-loaded SLNs were 300 to 800 nm and −18 to −32 mV, respectively. High drug entrapment efficiency in the narrow range of 80–85% was achieved. Cytotoxicity results indicated that cell growth inhibition of free drug and drug loaded nanoparticles is dose- and time-dependent. Inhalable dry powders prepared from drug-loaded SLNs were found to have a fine particle fraction in the range of 6.92±0.99 –11.24±2.4%, mean mass aerodynamic diameter in the range of 4.52±0.1 to 6.67±0.5 µm. The findings revealed that the proposed inhalable dry powder formulation loaded with erlotinib SLN has potential in lung cancer therapy through pulmonary route.
Keywords: drug delivery; bioavailability; anticancer drugs